APTANI: a computational tool to select aptamers through sequence-structure motif analysis of HT-SELEX data. (22nd September 2015) - Caroli, J.; Taccioli, C.; De La Fuente, A.; Serafini, P.; Bicciato, S.
Abstract : Motivation: Aptamers are synthetic nucleic acid molecules that can bind biological targets in virtue of both their sequence and three-dimensional structure. Aptamers are selected using SELEX, Systematic Evolution of Ligands by EXponential enrichment, a technique that exploits aptamer-target binding affinity. The SELEX procedure, coupled with high-throughput sequencing (HT-SELEX), creates billions of random sequences capable of binding different epitopes on specific targets. Since this technique produces enormous amounts of data, computational analysis represents a critical step to screen and select the most biologically relevant sequences. Results: Here, we present APTANI, a computational tool to identify target-specific aptamers from HT-SELEX data and secondary structure information. APTANI builds on AptaMotif algorithm, originally implemented to analyze SELEX data; extends the applicability of AptaMotif to HT-SELEX data and introduces new functionalities, as the possibility to identify binding motifs, to cluster aptamer families or to compare output results from different HT-SELEX cycles. Tabular and graphical representations facilitate the downstream biological interpretation of results. Availability and implementation: APTANI is available at http://aptani.unimore.it . Contact: silvio.bicciato@unimore.it Supplementary information: Supplementary data are available at Bioinformatics online.